The potential of integrating blockchain technology into smart sustainable city development - Tan, Xian Yi (2021)
The exponential growth of urban population has led to the urban challenges in political, economic, environmental and social aspects. This is mainly due to the inefficiency of existing built environment which is unable to meet the rising demand of population for basic amenities and resources. Hence, the implementation of smart sustainable city with the integration of blockchain technology has become an effective antidote to resolve and ameliorate the overwhelming urban issues. Numerous previous studies were conducted on blockchain technology and smart sustainable city. However, these studies generally focused on the overview of incorporating blockchain technology into smart sustainable city and there are limited existing studies that comprehensively analyse the potential applications of blockchain technology in smart sustainable city development in Malaysia context. Therefore, this study aims to investigate the potential of integrating blockchain technology into smart sustainable city development in Malaysia from construction practitioners’ perspectives. Seven smart applications of blockchain technology in smart sustainable city were identified such as Smart Governance, Smart Transportation, Smart Supply Chain Management, Smart Healthcare, Smart Education, Smart Asset and Smart Utility. Questionnaires were designed and distributed to the construction practitioners within Klang Valley and a total of 153 responses were collected. The data collected was analysed using Cronbach’s Alpha Reliability Test, Arithmetic Mean, Mann-Whitney U Test and Kruskal-Wallis Test. The findings revealed that Smart Healthcare is highly accepted by the construction practitioners and the Smart Governance is of utmost importance. Besides, there is no significant difference between genders in accepting the blockchain technology. The findings likewise showed that different age groups and educational levels have different acceptance levels on the applications of blockchain technology. The findings of this study are expected to make useful contributions by conveying the construction practitioners’ acceptance level towards the applications of blockchain technology and their perspectives on the importance of these applications to the local government and planners as well as the relevant implementing vi organisations and stakeholders in developing the framework for the smart sustainable city development in Malaysia.